Rasgos diferenciales fundamentales entre la Educación Bancaria y la Educación Liberadora en las pedagogías de J. Comenio y P. Freire - Avila Rodriguez, Angelica Maria (2022)
The present research aimed to determine the fundamental differential features between Banking Education and Liberating Education in the pedagogies of J. Comenio and P. Freire. For this, the comparative study was carried out between the Traditional Pedagogy of J. Comenio and the Liberating Pedagogy of P. Freire, defined as comparative units. The design of the research was descriptive-comparative, with the use of techniques and instruments such as bibliographic recording and information matrices, and the procedure based on the phases of the comparative method: description, interpretation, juxtaposition and comparison. The results obtained were the convergences and divergences found in the comparison of the comparative subunits corresponding to each comparative unit, and the fundamental differential features of anti-dialogue and dialogue, accommodation and insertion, dehumanization and humanization, based on the divergences found in the comparison. Finally, it was concluded that, first, anti-dialogue and dialogue, based on contradiction and conciliation between educators and students, respectively; second, accommodation and insertion, based on the immersion and awareness of students, respectively; and, finally, dehumanization and humanization, based on the conversion of students into objects and subjects, respectively, are the fundamental differential features between Banking Education and Liberating Education in the pedagogies of J. Comenio and P. Freire.